Computer and computing technologies in agriculture IX. 9th IFIP WG 5.14 International Conference, CCTA 2015, Beijing, China, September 27-30, 2015, Revised selected papers.: 9th IFIP WG 5.14 International Conference, CCTA 2015, Beijing, China, September 27-30, 2015, Revised selected papers. Part I : (2016) - Unknown
No abstract available